Gender Variation in the Intonation of Thanks and Gratitude in Iraqi Arabic - Abdul-Imam Al-Riyahi, Assist. Prof. Dr. Alaa (Basra studies journal, 2025)
Everyday speech is rich of various types of polite terms and utterances, such as address terms, greetings, thanks and gratitude, etc. used to maintain harmony and solidarity among the members of a community. Such expressions and terms are produced on various intonational patterns by different participants. The speech of 48 Iraqi Arabic speakers from the city center of Basrah is recorded to examine the intonational patterns of thanks and gratitude. The participants are divided into three groups: educated, partly educated and uneducated participants. Each group includes eight men and eight women. The intonational system of Halliday and Greaves (2008) is adopted to describe the intonational patterns used. The study concludes that thanks and gratitude in Iraqi Arabic are pronounced on various intonational patterns. They occur more frequently on falling tones than on rising tones. The variation in the use of intonational patterns being clearer in the case of partly education participants, whose female participants use rising tones more than the male participants. The examination of the intonation of Iraqi Arabic requires a modification of Halliday and Greaves‟ system of intonation (2008) by adding new symbols to account for the intonational patterns observed.